2022
DOI: 10.1093/oncolo/oyac094
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic and Genomic Landscape of Non-Small Cell Lung Cancer Brain Metastases

Abstract: Background In patients with non-small cell lung cancer (NSCLC), 10%-40% will eventually develop brain metastases. We present the clinicopathologic, genomic, and biomarker landscape of a large cohort of NSCLC brain metastases (NSCLC-BM) samples. Materials and Methods We retrospectively analyzed 3035 NSCLC-BM tested with comprehensive genomic profiling (CGP) during routine clinical care. In addition, we compared the NSCLC-BM to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 34 publications
4
14
0
Order By: Relevance
“…Next, we analysed sequencing data of primary lung tumours and metastatic sites of NSCLC patients [ 39 ]. Confirming our in vitro observations and in line with a recently published study by Huang et al [ 40 ], we found that NKX2–1 amplifications are enriched in brain, lymph node and liver metastatic sites compared to the primary lung tumours (Fig. 5h ).…”
Section: Resultssupporting
confidence: 93%
“…Next, we analysed sequencing data of primary lung tumours and metastatic sites of NSCLC patients [ 39 ]. Confirming our in vitro observations and in line with a recently published study by Huang et al [ 40 ], we found that NKX2–1 amplifications are enriched in brain, lymph node and liver metastatic sites compared to the primary lung tumours (Fig. 5h ).…”
Section: Resultssupporting
confidence: 93%
“…4A-C). Of note, the most prevalent genetic changes across all targetable somatic changes were EGFR, followed were CDKN2A and KRAS mutations, and the distribution of actionable mutation spectrum was similar to that in NSCLC cohort in some other study [26,27]. In our oligometastatic cohort, all the potential drugs targeting specific genetic alterations were also presented in Fig.…”
Section: A C C E P T E D a R T I C L E Korean Cancer Associationsupporting
confidence: 69%
“…According to the results of univariate Cox analysis, the pathological T,N,M stages as well as brain metastasis are not factors related to survival whether the tumour exceeds 7 cm, with the presence or absence of pulmonary nodules’ and having proximal or distal metastasis. We chose to consider brain metastasis as an independent metastasis factor because shreds of evidence suggest that 20%–40% of LC patients will develop brain metastasis and 10% of non-small cells LC (NSCLC) patients are diagnosed with it at first LC discovery [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%